DETERMINATION OF FERTILITY AND POLLEN VIABILITY OF BREEDING LINE OF PATTYUPAN SQUASH WITH MALE STERILITY OF FUNCTIONAL TYPE - A. M. Shantasov; S. D. Sokolov; A. V. Bocharnikov; V. A. Maletina (Овощи России, 2015)
This article describes the features of the development of male sterility trait of functional type in patty"pan squash. The viability of pollen grains in different periods of vegetation was studied. The determined fertility ability of pollen can be used for hybrid seed production of different varieties of pumpkin.